Effect of use and type of helmet on occurrence of traumatic brain injuries in motorcycle riders in Korea: a retrospective cohort study - Sowon Seo; Seok Ran Yeom; Sung-Wook Park; Il Jae Wang; Suck Ju Cho; Wook Tae Yang; Youngmo Cho (Journal of Trauma and Injury)
Purpose The purpose of this study was to investigate (1) the association among helmet wearing, incidence rate of traumatic brain injury (TBI), and in-hospital mortality; TBI was diagnosed when the head Abbreviated Injury Scale (AIS) was ≥1, and as severe TBI when head AIS was ≥3; and (2) the association between helmet type and incidence rate of TBI, severe TBI, and in-hospital mortality of motorcycle accidents based on the newly revised Emergency Department-based Injury In-depth Surveillance (EDIIS) data. Methods Data collected from EDIIS between January 1, 2020 and December 31, 2020 were analyzed. The final study population comprised 1,910 patients, who were divided into two groups: helmet wearing group and unhelmeted group. In addition, the correlation between helmet type and motorcycle accident was determined in 596 patients who knew the exact type of helmet they wore. A total of 710 patients who wore helmet but did not know the type were excluded from this analysis. Multivariate logistic regression was performed in both the groups to investigate the factors affecting the primary (occurrence of TBIs) and secondary outcomes (severe TBI and in-hospital mortality). Results The prevalence of Injury Severity Scores, TBIs, and severe TBIs as well as in-hospital mortality were the highest in the unhelmeted group. Additionally, the results from the group that wore and knew the type of helmet worn indicated that wearing a full-face helmet decreased the incidence of TBIs in comparison to a half-face helmet. Conclusions The wearing of a helmet in motorcycle accidents is very important as it plays a role in reducing the occurrence of TBIs and severe TBIs and in-hospital mortality. The use of a full-face helmet lowered the incidence of TBIs.